Assessment of Acoustical Level in Healthcare Design: In Comparison with the Standards of World Health Organization - Akmal, Asma; Laeeque, Bisma; Niazi, Nabeela; Khaleeq-ur-Rahman, Muhammad; Akmal, Asma (Nurture, 2019)
This research was undertaken to assess acoustical conditions in the hospital environment, researcher aimed at investigating sound levels of local hospitals and to evaluate how much their current status complied with recommendations levels given by World Health Organization. To assess the actual noise impact, sound levels of six local hospitals were measured using non – probability sampling technique at five different locations of every hospital i.e. Waiting Area, Emergency Department, Corridor, Intensive Care Unit and General Ward. All readings obtained during morning, afternoon and night intervals were then compared with World Health Organization acoustic guidelines for hospitals (30-40dB) Findings revealed that sound levels of all hospitals studied were significantly high as compared to standards given by WHO, the hypothesis was significant with p<.005, twice as high sound levels were observed in comparison to the recommended limits. Equivalent continuous sound levels (Leq) in most hospitals of Lahore ranged between (70-80dB), irrespective of time of the day, indicating a serious issue of noise pollution. Results also indicated that the highest sound levels were observed in waiting area at Hameed Latif hospital (110dBA). While the lowest sound levels were observed in Intensive Care Unit of Sheikh Zayed hospital (59dBA), which despite being the lowest were high in comparison to standards given by World Health Organization. Furnishings and interiors of a hospital usually have easy-to-clean surfaces that are hard and reflective in order to prevent infections, but such surfaces tend to propagate noise into the patient rooms and down the corridors causing sound to reverberate. Optimal sound levels in hospitals can only be achieved through regular sound assessment, proper zoning of high and low activity areas and use of sound absorbing materials in building design that do not compromise hygiene requirements of the place. Only then patients can truly receive the quality of care they deserve.